Entomofauna em áreas em estágio inicial de restauração florestal sob diferentes tipos de controle de plantas indesejáveis e uso de fertilizantes - Providello, Alexandra (2021)
In the forest restoration process, it is important to measure the recovery efficiency of ecological processes. Due to their abundance and diversity and quick responses to environmental variations, insects can be used as bioindicators of the ecological restoration process, but little is known about how they respond to usual management practices in forest restoration. The objective of this work was to test the hypothesis that different types of undesirable plant control and the use of fertilizers influence forest restoration and, consequently, the entomofauna dynamics in an area at an early stage of forest restoration. The study was conducted in a forest restoration area in the city of Araras in the state of São Paulo. The experimental design was completely randomized in a split-plot scheme, submitted to four treatments: intensive control of undesirable plants with fertilizers (I+F+); intensive control of undesirable plants without fertilizers (I+F-); non-intensive control of undesirable plants with fertilizers (I-F+); non-intensive control of undesirable plants without fertilizers (I-F-). The entomofauna was collected using pan and pitfall traps, in three periods: July 2019 (dry) and January (rainy) and July (dry) 2020. Pan traps (yellow, blue, white and red) and pitfalls were placed in the center of each subplot, totaling six traps per treatment. Both remained in the field for 120 hours. The vegetation parameters analyzed were basal area and distance from the study area in relation to a reference forest fragment. Initially, the analysis of variance (ANOVA) was performed to verify a possible interaction between the type factors of undesirable plant control and fertilizer use on the entomofauna and vegetation variables. As it was not significant, the factors were analyzed separately, and their levels were compared using the Tukey test. In total, 16,001 specimens were collected, distributed in 11 orders and 64 families. Only the control of undesirable plants influenced the abundance and richness of the entomofauna and the basal area of the trees. The entomofauna was more abundant and richer in the intensive control, however, the basal area was bigger in the non-intensive control. Only entomofauna richness was positively related to basal area. The use of fertilizers did not significantly influence neither the basal area nor the entomofauna. Distance from the study area in relation to a reference forest fragment did not show a significant relationship with any of the entomofauna variables. In the present study, it was observed that different types of undesirable plant control influence the growth of the restoration tree community and, consequently, the abundance and richness of the entomofauna. There is a positive relationship of the basal area only with the richness of the entomofauna. At the taxonomic identification level used, the entomofauna could not be adopted as a secondary measurement parameter for the forest restoration process.